Delaying latency to hyperbaric oxygen‐induced CNS oxygen toxicity seizures by combinations of exogenous ketone supplements. Issue 1 (3rd January 2019) - Ari, Csilla; Koutnik, Andrew P.; DeBlasi, Janine; Landon, Carol; Rogers, Christopher Q.; Vallas, John; Bharwani, Sahil; Puchowicz, Michelle; Bederman, Ilya; Diamond, David M.; Kindy, Mark S.; Dean, Jay B.; et al.
Abstract: Central nervous system oxygen toxicity (CNS‐OT) manifests as tonic‐clonic seizures and is a limitation of hyperbaric oxygen therapy (HBOT), as well as of recreational and technical diving associated with elevated partial pressure of oxygen. A previous study showed that ketone ester (1, 3‐butanediol acetoacetate diester, KE) administration delayed latency to seizures (LS) in 3‐month‐old Sprague‐Dawley (SD) rats. This study explores the effect of exogenous ketone supplements in additional dosages and formulations on CNS‐OT seizures in 18 months old SD rats, an age group correlating to human middle age. Ketogenic agents were given orally 60 min prior to exposure to hyperbaric oxygen and included control (water), KE (10 g/kg), KE/2 (KE 5 g/kg + water 5 g/kg), KE + medium‐chain triglycerides (KE 5 g/kg + MCT 5 g/kg), and ketone salt (Na + /K + β HB, KS) + MCT (KS 5 g/kg + MCT 5 g/kg). Rats were exposed to 100% oxygen at 5 atmospheres absolute (ATA). Upon seizure presentation (tonic‐clonic movements) experiments were immediately terminated and blood was tested for glucose and D ‐beta‐hydroxybutyrate ( D ‐ β HB) levels. While blood D ‐ β HB levels were significantly elevated post‐dive in all treatment groups, LS was significantly delayed only in KE ( P  = 0.0003), KE/2 ( P  = 0.023), and KE + MCT ( P  = 0.028) groups. In these groups, the severity of seizures appeared to be reduced, although these changes were significant only in KE‐treated animals ( P  = 0.015). Acetoacetate (AcAc) levels were also significantly elevated in KE‐treated animals. The LS in 18‐month‐old rats was delayed by 179% in KE, 219% in KE + MCT, and 55% in KE/2 groups, while only by 29% in KS + MCT. In conclusion, KE supplementation given alone and in combination with MCT elevated both β HB and AcAc, and delayed CNS‐OT seizures. Abstract : The specific aim of this study was to expand upon previous research establishing the link between therapeutic ketosis and the resulting antiseizure effects. We hypothesized that ketogenic strategies that elevate both β HB and AcAc would have the greatest potential delaying CNS‐OT. Thus, we explored the effect of different dosages and combinations of exogenous ketone supplements on CNS‐OT seizures in an age group of male Sprague‐Dawley rats (18 months) that is used to model middle age in humans. In conclusion, ketone ester supplementation given alone and in combination with MCT elevated both blood β HB and AcAc levels and delayed CNS‐OT seizures.